Reconstructing Legal Protection Regulations for Parties in Franchise Agreements Based on Dignified Justice - Suhaila Zulkifli; Tajuddin Noor (Khazanah Hukum, 2024)
Franchise agreements are recognized globally and Indonesia is experiencing significant growth in this industry. However, weaknesses in existing regulations, particularly Government Regulation No. 42 of 2007 and Minister of Trade Regulation No. 71 of 2019 hinder legal certainty and protection for franchisors and franchisees. This research aims to reconstruct Article 8 of Government Regulation No. 42/2007 on franchising to improve legal certainty and protection and promote justice for all parties involved. A critical review of Article 8 of Government Regulation No. 42/2007 reveals an ambiguity in the term ‘sustainable’, which can lead to various interpretations and potential legal conflicts. The research findings show that adding the word ‘periodically’ before the word ‘sustainable’ in Article 8 will provide clearer guidelines for franchisors regarding their obligation to guide the form of training, operational management, marketing, research, and development to franchisees. Using the normative juridical method, this research analyses secondary data from relevant laws and regulations. The insights gained can inform policymakers and stakeholders on reforms that need to be made to improve legal clarity. Implementing these recommendations may result in a more balanced power dynamic between franchisors and franchisees, which may ultimately contribute to the sustainable growth of the franchise industry in Indonesia. In conclusion, addressing vagueness in franchise agreements is critical to creating a fair business environment, and bringing dignified justice to the parties. Clarity in regulation will not only protect the rights of franchisors and franchisees but also promote the growth and stability of the franchise sector in Indonesia.